FAKTOR – FAKTOR INTERNAL KETIDAKPATUHAN PENGOBATAN HIPERTENSI DI PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Ajeng Sri Pujasari; Henry Setyawan Susanto; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2017)
Non-compliance is cause of treatment failure. Non-compliance treatment often occurs in patients with chronic diseases for example hypertension. Hypertension is defined as raised systolic or diastolic blood pressure more than 140/90 mmHg. Adherence treatment of hypertension assessed on pharmacological and non-pharmacological treatment. Internal factors affecting adherence to treatment include age, sex, level of education, employment, knowledge, duration of sufering, duration of treatment, number of antihypertensive drugs taken, and side effects of drugs. This research aim to know internal factors related with Non-compliance in the treatment of hypertensive patients.This research was observational-analytic with cross-sectional approach. Samples were 128 samples chosed with consecutive sampling. Instrument research was questionnaire. Data was analysed with chi-square for bivariate analysis dan regression logistic for multivariat analysis with 95% CI. Bivariate analysis there were not significant association between age (p=0,811), sex (p=0,396), employment (p=0,248), duration of sufering (p=0,081), number of antihypertensive drugs taken (p=0,467) dan and side effects of drugs (p=0,182), but there were significant association between level of education (p= <0,0001), knowledge (p= < 0,0001; 95% CI=24,21-307,10; POR=86,2) and duration of treatment (p=0,003). Multivariate analysis there were significant association between knowledge (p= < 0,0001) dan duration of treatment (p=0,025; 95% CI=0,04-0,81; POR=0,2). We conclude that significant association between knowledge and duration of treatment with non-compliance in the treatment of hypertensive patients. Suggestions for the officer can increase patient knowledge and treatment of hypertension-related diseases that the patient can undergo treatment for a long period even a lifetime.